Study of the Pepsin Enzymatic Activity in in-vitro Dissolution Test of Bromazepam Tablets by UV/VIS Spectrophotometry - Guilherme Nobre Lima do Nascimento,Eurico Viegas Montalvao and Tales Alexandre Aversi-Ferreira (Journal of Applied Pharmaceutical Science)
The in vitro dissolution test is an essential parameter to determine the properties of biopharmaceutical formulations. Therefore, the purpose of this study was to evaluate the dissolution of solid Bromazepam formulations and different enzyme concentrations. The dissolution test for Bromazepam tablets was performed using a Vankel VK 7000, apparatus 2 (paddle), at temperature of 37.0°C. The dissolution medium simulated gastric fluid with pepsin, which was prepared with 2 g of sodium chloride, varying concentrations of purified pepsin and 7 mL of hydrochloric acid (PA) in 1000 mL of water. The pH was maintained close to 1.2. The results obtained in the dissolution test showed that the samples have been influenced by the presence of pepsin for both similar drug and reference drug. Among the various enzyme concentrations tested, the highest enzyme concentration tested showed the best results. Thus, it could be concluded that the increase in enzyme concentration increases the dissolution of both drugs, causing a decrease in the test time.